2014
DOI: 10.1136/jnnp-2013-307515
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and time to relapse after discontinuing 6-month therapy with IVIg or pulsed methylprednisolone in CIDP

Abstract: A similarly high proportion of patients treated with IVIg or IVMP eventually relapse after therapy discontinuation but the median time to relapse was significantly longer after IVMP than IVIg. This difference may help to balance the more frequent response to IVIg than to IVMP in patients with CIDP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 23 publications
(27 reference statements)
0
56
0
5
Order By: Relevance
“…In 1 series, 25% of patients remained in remission after a mean follow‐up of 4 years . Further recently published data have similarly suggested remission rates of about 20% . Considerably higher remission rates have also been reported, ranging from 30% to 47% .…”
Section: Ivig For Cidp: For How Long?mentioning
confidence: 85%
See 1 more Smart Citation
“…In 1 series, 25% of patients remained in remission after a mean follow‐up of 4 years . Further recently published data have similarly suggested remission rates of about 20% . Considerably higher remission rates have also been reported, ranging from 30% to 47% .…”
Section: Ivig For Cidp: For How Long?mentioning
confidence: 85%
“…Despite the lack of evidence of greater efficacy in severe disease, it may be argued that IVIg, in view of the latest trial data, represents a more justified first choice if function is severely impaired, because it offers a higher likelihood of side‐effect‐free therapeutic response in the short term. However, in cases with relatively mild functional disability, not urgently requiring rapid improvement and without contraindication to corticosteroids, the latter may need to be considered as first line, given the possible greater chance of future relapse‐free treatment withdrawal, or a longer period of remission . IVIg is an appropriate second‐line option in these patients if the steroid response is inadequate or if side‐effects occur.…”
Section: Some Proposals For Clinical Practicementioning
confidence: 99%
“…Upon withdrawal of the maintenance treatment, the relapse rate is high: 45% with IVIg and 50% with oral corticosteroids in the 6 months following interruption. In a recent trial, comparing IVIg to methylprednisolone, a similarly high proportion of relapses after discontinuation (87%) was found in the two groups, even if the median time to relapse was significantly longer after methylprednisolone than after IVIg . Consequently, around 40% to 65% of patients require a maintenance treatment and become dependent on the treatment in the long term .…”
Section: Introductionmentioning
confidence: 92%
“…After 12 months, 54% of IVIG‐treated subjects did not require further therapy. Long‐term follow‐up of IVIG‐treated subjects revealed that approximately 86% would worsen within a median follow‐up time of 42 months (range 1–57 months) after therapy discontinuation (median time to worsening 4.5 months, range 1–24 months) …”
Section: Discussionmentioning
confidence: 99%